Portrait of Flora - unknown:::Creator::::::::::::
Flora Woods Adams b.1877 - d.1948 07. She is the model for the characters Dora Williams in Tortilla Flat, Flora/Fauna in Sweet Thursday, Dora Flood in Cannery Row, and Faye in East of Eden. Flora was the proprietress and madame of several Monterey restaurants/bordellos, including The Lone Star Cafe, The Golden Stairs, The Golden Restaurant, and The Quick Lunch.